Geriatric Depression and Variables in Residential Homes Located around Religious Beliefs Tagged Land Area - Poudel, Prakar; Timalsina, Santosh; Rimal, Sabin (Nepal Journal of Multidisciplinary Research, 2022)
Depression is one of the psychiatric problems in geriatric population with a decrease in wellbeing. There was few prevalence studies carried out in old age residential homes located around spiritual and religious beliefs’ tagged area. This study was to find prevalence of depression and its associations in residents of old-age homes located around spiritual and religious beliefs’ tagged area. A cross-sectional study was carried out in four residential homes with face-to-face interviews using validated GDS-15 and PHQ-9 Nepali version questionnaires. Data were analyzed using percentage, mean, univariate analysis and logistic regression. Among a total of 108 respondents, GDS-15 screening detected 36.2% of residents to be depressed (cut-off 4/5) and PHQ-9 screening detected 37.1% to be depressed (cut-off 4/5). The mean age was 75.7 years (± 8.3). Two-thirds of residents were female and the majority follow Hinduism religion. The majority were illiterate and were farmers in past. Odds of having depression decreases by 92% in self-reported better-satisfied status compared to unsatisfied status and by 89% in self-reported better-financed status compared to worse financed status. Geriatric depression is low in old age homes located around areas tagged with religious and spiritual beliefs. However further comparative study is required to find a correlation of depression with spirituality and religiousness in daily social living. Depression decreases more with self-satisfaction of old age people rather than financial stability.